The Charter and Ordinances of the City of Providence, with the Acts of the General Assembly Relating to the City, at 60, Ordinances of the City of Providence, Fire-arms. An Ordinance in Relation to the Firing of Guns, Pistols and other Fire-arms, § 1 (1835) - (:unkn) unknown (My University, 1835)
No person shall fire any gun, pistol, rifle or other fire-arm, in any street or lane, or on any public wharf, or on any public lands within said city, after sunrise and before sunset
Keywords: DISCHARGE